2019
DOI: 10.1111/pbr.12753
|View full text |Cite
|
Sign up to set email alerts
|

QTL mapping and effect confirmation for anaerobic germination tolerance derived from the japonica weedy rice landrace PBR

Abstract: As one of the main rice establishment methods, direct seeding has the advantages of saving labour and reducing costs for farmers. However, the expansion of direct seeding has been constrained by poorly levelled fields, heavy rainfall and poor drainage after sowing. The development of cultivars with anaerobic germination tolerance could improve or overcome these shortcomings of most rice under flooding conditions. In this study, a japonica‐type rice with anaerobic germination tolerance was suggested as a new ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The Korean weedy rice, photoblastic rice (PBR), was identified with potential for anaerobic condition survivability with high germination percentage [ 104 ]. Jeong et al [ 105 ] developed a mapping population using PBR, and the authors reported three QTLs involved in imparting tolerance of flooding: qAG1 , qAG3 , and qAG11 . Other genes have also been reported, such as the QTLs qAG-9–2 ( AG1 ) and qAG-7–2 ( AG2 ) [ 106 ].…”
Section: Stress During Germinationmentioning
confidence: 99%
“…The Korean weedy rice, photoblastic rice (PBR), was identified with potential for anaerobic condition survivability with high germination percentage [ 104 ]. Jeong et al [ 105 ] developed a mapping population using PBR, and the authors reported three QTLs involved in imparting tolerance of flooding: qAG1 , qAG3 , and qAG11 . Other genes have also been reported, such as the QTLs qAG-9–2 ( AG1 ) and qAG-7–2 ( AG2 ) [ 106 ].…”
Section: Stress During Germinationmentioning
confidence: 99%
“…A novel QTL ( qACE3.1 ) was identified for coleoptiles elongation under anaerobic condition in the population of chromosome segment substitution lines (CSSL S ) substituted with Koshihari in IR64 genetic background [ 130 ]. Three QTLs ( qAG1 , qAG3 and qAG11 ) were identified from a study carried out by Jeong et al [ 131 ] by using 188 RILs from a cross between PBR (Photo-blastic Rice) as a donor and ‘Nampyeong’, a Korean japonica cultivar. Among different anaerobic germination QTLs identified till now, the QTL ( qAG.9.2 ) is pinned down to AG1 gene, responsible for coleoptile elongation during anaerobic germination.…”
Section: Genetic Basis Of Flooding Tolerance In Ricementioning
confidence: 99%
“…Submergence tolerance is another characteristic greatly variable in weedy rice, while in many cultivated varieties poor seedling establishment often occurs in case of heavy rainfall, poor drainage or in uneven field levelling [112]. The unfavorable submergence conditions may result in high yield losses in rice [112].…”
Section: Drought and Submergencementioning
confidence: 99%
“…Submergence tolerance is another characteristic greatly variable in weedy rice, while in many cultivated varieties poor seedling establishment often occurs in case of heavy rainfall, poor drainage or in uneven field levelling [112]. The unfavorable submergence conditions may result in high yield losses in rice [112]. During flooding, seeds have to germinate in low aerobic conditions, which limit the respiration, creating an unsuitable environment for germination and seedling growth [113].…”
Section: Drought and Submergencementioning
confidence: 99%
See 1 more Smart Citation